Упростите 5√6 (3√6+√216); (2√3-√7) 2; (3√2-√5) (√5+3√5); 1/3√18+3√72-√98

+2
Ответы (1)
  1. 6 июля, 23:30
    0
    1) 5 * √6 * (3 * √6 + √216) = 5 * (√6 * 3 * √6 + √6 * √ (54 * 4)) =

    = 5 * (6 * 3 + √6 * √ (9 * 6 * 4)) = 5 * (18 + √6 * √6 * √9 * √4) =

    = 5 * (18 + 6 * 3 * 2) = 5 * (18 + 18 * 2) = 5 * 18 + 5 * 18 * 2 =

    90 + 90 * 2 = 270;

    2) (2 * √3 - √7) ² = (2 * √3) ² - 2 * 2 * √3 * √7 + (√7) ² = 4 * 3 - 2 * 2 * √3 * √7 + 7 =

    = 12 + 7 - 4 * √3 * √7 = 19 + 4 * √21;

    3) (3 * √2 - √5) * (√5 + 3 * √5) = 3 * √2 * √5 + 3 * √2 * 3 * √5 - √5 * √5 - 3 * √5 * √5 =

    3 * √2 * √5 + 9 * √2 * √5 - 3 * 5 - 5 = 12 * √10 - 20;

    4) 1/3 * √18 + 3 * √72 - √98 = 1/3 * √ (9 * 2) + 3 * √ (36 * 2) - √ (49 * 2) =

    = 1/3 * 3 * √2 + 3 * 6 * √2 - 7 * √2 = √2 * (1 + 18 - 7) = 12 * √2.
Знаешь ответ на этот вопрос?